Eksperimen dan Perannya dalam Pemahaman Konsep Fisika - Imam Sutaji, Hadi; Warsito, Ali; Bernandus, Bernandus (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
In IPA learning, especially physics, in addition to understanding theoretical physics concepts, student involvement through direct experience in learning as an actualization of the knowledge learned is very necessary. This actualization is realized through experimental activities that are expected to help students understand physics concepts more easily, more quickly, and longer remember them so that students are motivated to study physics further. Physics experimental activities can be carried out at various levels of education units, from Elementary School (SD)/equivalent, Junior High School (SMP)/equivalent, and Senior High School (SMA)/equivalent. Especially for Senior High School (SMA), students already have the ability to think abstractly, logically, and critically so that direct experience in learning physics will help improve these abilities. One such experience is experimentation. The existence of experiments will present natural phenomena as characteristics of physics into something easy to understand so that it is not only theoretical in its delivery. In this Community Service Activity, experiments are presented in physics learning. The results of the activity evaluation gave a positive response to the implementation of the activity, where students felt helped to understand several physics concepts through the role of the experiments that have been carried out so that students have a sense of interest and motivation to study IPA, especially physics further.